The Relationship Between Family Resilience and The Role of Peers on Reproductive Health Behaviour in Adolescents at SMPN 258 East Jakarta - Taftahzani, Salsa Billa; Ritanti, Ritanti (jitek, 2023)
Reproductive health issues are still a significant problem among adolescents, such as free sex, abortion, sexually transmitted infections, and HIV/AIDS, requiring government attention. One of the causes is the inadequate family resilience of adolescents and the influence of peers. This study aimed to determine the relationship between family resilience and the role of peers on reproductive health behaviour in adolescents at SMPN 258 East Jakarta. The research design used a cross-sectional approach with a proportionate stratified random sampling technique. This research was conducted in May 2023. This study's population were adolescents still active at SMPN 258 Jakarta. A total of 250 adolescents participated in this study. From the Chi-square test results, it was found that there was a relationship between family resilience and the role of peers on adolescent reproductive health, with a p-value of family resilience of 0.002 (p<0.05) and the part of peers of 0.003 (p<0.05). The researcher recommends this study as a policy basis to the DKI Jakarta Health Office regarding the importance of understanding, assistance, and supervision from parents regarding adolescent reproductive health and to the school by providing counselling on choosing good peers.